Facile Synthesis of Pyrido[2,1-a]isoindoles via Iron-Mediated 2-Arylpyridine C–H Bond Cleavage - Liu, Shan; Hu, Xingen; Li, Xinhua; Cheng, Jiang (Synlett, 2013)
An iron-catalyzed reaction of 2-arylpyridine C–H bond with 2-bromoacetophenone is achieved, providing pyrido[2,1-a]-isoindoles in moderate to good yields. The regioselectivity stems from the domination of hindrance on the regioselective ortho-functionalization of 2-arylpyridines C–H bond.
Keywords: iron; 2-arylpyridine; C–H bond cleavage; pyridoisoindole; regioselectivity